Design and control of three-phase four-wire T-type inverters - Teh, Zhi Yu (Nanyang Technological University, 2024)
With the movement towards carbon neutrality, renewable energy has been a popular solution to that end. However, renewable energy sources produce Direct Current (DC) power while electrical appliances operate using Alternating Current (AC) power. Hence, inverters, also known as DC-to-AC Converters, is needed to convert power from DC to AC. Inverters mainly consist of four stages: the bridging circuit stage which can be accomplished using the H-Bridge or T-Type topology, the Pulse Width Modulation (PWM) stage which controls the turning on and off of the switches, the LCL filter stage which lowers the total harmonic distortion of the output and the control stage which balances the three-phase output.